PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ISPRING MELALUI PENDEKATAN SAINTIFIK MATERI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN PADA KELAS IV SDN PAKUNDEN 1 - Saniah, Khoirotul Binti; Farida Nurlaila Zunaidah; Mumun Nurmilawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce ispring-based interactive media that is suitable for use to assist learning activities in science subjects regarding the structure and function of plant parts. The method used in this research is the Research and development (R&D) method using the ADDIE model. The subjects taken in this research were 16 class IV students at SDN Pakunden 1, Kediri city. The data collection technique in this research is by using a questionnaire. The results of this research obtained a validity assessment according to media expert validators in the appearance aspect of layout design, text, images and animation, obtaining a percentage score of 84.6% with the criteria "Very Valid". According to the material expert validator, the aspects of appropriateness of content, appropriateness of language, and appropriateness of presentation obtained a percentage score of 84% with the criteria "Very Valid". This result is supported by the students' responses by obtaining a percentage score of 92.5% which is the "Very Practical" criterion, and the teacher's response obtained a percentage score of 88% which is the "Very Practical" criterion. This is also proven by the results of evaluation questions from students after using Ispring-based interactive media on the structure and function of plant parts, namely obtaining a percentage of 85.1% with the criteria "Very Effective". Thus it is concluded that Ispring-based interactive media is very valid, practical and effective for use in the learning process.